YOUNG ADULT DYSTOPIAN AND GENDER IDENTITY: A STUDY OF THE LEGEND (2011) TRILOGY - Luthfia Ridzka Latiffa; Bayu Kristianto (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2022)
There is no doubt that young adult dystopian novels are popular among their audience. Young adult dystopian novels offer readers a fictional medium to reimagine societal values, including, but not limited to, gender. In the 2010s, titles such as The Hunger Games, Divergent, and Legend rose to fame as they amassed millions of readers, further strengthening the genre’s popularity and influence among young adults. This article will specifically analyze the Legend (2011) trilogy by Marie Lu, a series of dystopian novels set in the post-apocalyptic United States. Using concepts of gender binary opposition and possibilities-potentialities, this article aims to uncover the trilogy’s attempt at reconstructing gender identity by presenting non-traditional roles in its story, notably in its depiction of the main character and supporting characters. The article will identify gendered representations within the trilogy, analyze whether the representations are consistent throughout the story, and study its underlying message concerning values present in the real world. Based on the analysis, this article found that the Legend trilogy tend to reproduce existing realities that already exist in the real world. However, it still offers a layered, non-traditional representation of both masculine and feminine gender identity through its characters. AbstrakTidak ada keraguan bahwa novel distopia dewasa muda (young adult) merupakan novel yang populer di kalangan pembacanya. Novel distopia dewasa muda memberikan pembaca medium fiksi untuk membayangkan ulang nilai-nilai sosial, termasuk juga, namun tidak terbatas pada, gender. Pada tahun 2010-an, judul-judul seperti The Hunger Games, Divergent, dan Legend naik daun karena mereka mengumpulkan jutaan pembaca, yang memperkuat popularitas dan pengaruh genre tersebut di kalangan para dewasa muda. Artikel ini akan secara khusus menganalisis trilogi Legend (2011) karya Marie Lu, serangkaian novel distopia yang berlatar belakang di Amerika Serikat pasca-apokaliptik. Dengan menggunakan konsep oposisi biner gender dan potensi-kemungkinan, artikel ini bertujuan untuk mengungkap upaya trilogi ini dalam merekonstruksi identitas gender dengan menyajikan peran-peran non-tradisional dalam ceritanya, terutama dalam penggambaran karakter utama dan karakter pendukung. Artikel ini akan mengidentifikasi representasi gender dalam trilogi, menganalisis apakah representasi tersebut konsisten sepanjang cerita, dan mempelajari pesan tersembunyi terkait nilai-nilai yang ada dalam dunia nyata. Berdasarkan hasil analisis, artikel ini menemukan bahwa trilogi Legend cenderung mereproduksi realitas yang sudah ada di dunia nyata. Namun, artikel ini masih menawarkan representasi identitas gender maskulin dan feminin yang kompleks melalui karakter-karakternya.